Serum Vitamin D and Cardiometabolic Markers: A Comparative Study in Adult Men Based on Body Mass Index - Shah, Syed Imran Ali; Iqbal, Sabiha; Sikandar, Mirza Zeeshan; Qazi, Umair Yaqub; Haq, Inamul (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Deficiency of vitamin D has been implicated in several disorders, including skeletal, immune, neural, metabolic, and cardiovascular diseases (CVDs). The impact of vitamin D deficiency on CVDs is potentially through derangement of cardiometabolic profile. The present work assessed the relationship between serum vitamin D levels and cardiometabolic markers in adult men. MATERIALS AND METHODS: A cross-sectional analytical study (n=160) was conducted on adult men between the ages 35-50 years without a history of CVDs and/or diabetes, liver, or kidney disorders. Serum vitamin D, lipid profile (cholesterol, triacylglycerol; TAG, low[1]density lipoprotein; LDL, high-density lipoprotein; HDL), and renal function tests (urea, creatinine) were measured using enzyme‑linked immunosorbent assays (ELISA). Pearson’s correlation was used for assessing correlations between the studied parameters. Participants were further grouped as underweight, normal weight, overweight, and obese based on their BMI values, and one-way ANOVA and post-hoc Tukey’s tests were done to observe group mean differences. RESULTS: Vitamin D and HDL were positively correlated (r=0.395, p=0.000) while negative correlation of serum vitamin D levels was seen with TAG (r=-0.539, p=0.000), cholesterol (r=-0.325, p=0.000), LDL (r=-0.541, p=0.000) and urea (r=-0.514, p=0.000). Levels of serum vitamin D (p=0.000) and HDL (p=0.000) were lower while levels of TAG (p=0.000), cholesterol (p=0.000), LDL (p=0.000) and urea (p=0.000) were higher in the overweight and obese groups. CONCLUSION: Inadequate serum vitamin D status is associated with dyslipidaemia in adult men. Moreover, obese and overweight men have lower serum vitamin D levels with pronounced dyslipidaemia, thus highlighting vitamin D as a potential cardiometabolic risk factor.